2004
DOI: 10.1016/j.accreview.2004.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Incremental prognostic value of troponin I and echocardiography in patients with acute pulmonary embolism

Abstract: Background To test the hypothesis that troponin I and echocardiography have an incremental prognostic value in patients with pulmonary embolism (PE). Methods and resultsIn 91 patients with acute PE, echocardiography was performed within 4 h of admission. Troponin I levels were obtained on admission and 12 h thereafter. The 0.06 µg/l troponin I cut-off level was identified as the most useful, high-sensitivity cut-off level for the prediction of adverse outcome by receiver operating characteristic analysis with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 11 publications
5
48
0
8
Order By: Relevance
“…It is worth noting that in our sample, of the patients with normal RV function (n = 41, 46% of the study population), 28% had elevated cTnI. A previous study demonstrates that a normal, rather than an abnormal echocardiographic examination offers the most valuable and additive information for risk stratification in PE [11].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It is worth noting that in our sample, of the patients with normal RV function (n = 41, 46% of the study population), 28% had elevated cTnI. A previous study demonstrates that a normal, rather than an abnormal echocardiographic examination offers the most valuable and additive information for risk stratification in PE [11].…”
Section: Discussionmentioning
confidence: 92%
“…In our study, RV dysfunction did not predict development of hemodynamic instability independent of elevated cTnI and of the clinical prognostic risk score. The finding may be surprising, given the information available in the 189 -2LL -2Log-Likelihood ratio a All multivariate models were adjusted for a variable indicating the time to optimal anticoagulation from admission literature [10,11] consolidated in a recent meta-analysis [3] on the independent prognostic role of RV dysfunction in PE. We found that RV dysfunction was related to the risk of development of hemodynamic instability in a univariate model, and in a multivariate model including clinical prognostic score but not cTnI (hazard ratio 3.2, 1.1-5.9 vs. development of hemodynamic instability).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although echocardiographic criteria for RV dysfunction differ among studies [5,18,19], we evaluated RV hypokinesia as an index of RV dysfunction in accordance with the ICOPER [1].…”
Section: Discussionmentioning
confidence: 99%
“…The association of elevated troponin and right ventricle dysfunction predicts mortality even in normotensive patients (HR 5.6; 95% CI 1.2-25.9). The incremental prognostic value of right ventricular dysfunction at echocardiography and elevated troponin levels are confirmed in a study in 91 patients with pulmonary embolism [58]. In this study, the ability of predicting in-hospital outcome by troponin and echocardiography, calculated by the area under the receiveroperating characteristic (ROC) curve from multivariate regression models, is incremental: 0.77 without including troponin I and echocardiography, 0.89 with troponin I alone, 0.86 with echocardiography alone, and 0.90 with the combination of troponin and echocardiography.…”
Section: Prognostic Stratification: Cardiac Biomarkersmentioning
confidence: 82%